PENGARUH HEDONIC VALUE TERHADAP BEHAVIORAL INTENTION DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA: 1903 – HERITAGE DINING) - Kevin Khuana (Jurnal Strategi Pemasaran, 2016)
This study aims to analyze the influence of Hedonic Value ( Adventure Shopping , Social shoping , Gratification Shopping , Idea Shopping , Role Shopping , Value Shopping) against Behavioral Intention ( Loyalty to the company, propensity to switch , Willingness to pay more , External response to the problem , internal response to the problem ) by considering factors Restaurant Customer Satisfaction ( Pace of Service, Service Overall , Server Communication & accurancy , taste & quality Food , Food Preparation , Gratefulness , Atmosphere in whole ). This study used a questionnaire which was distributed to 100 consumer respondents in 1903 - Heritage Dining. With PLS analysis technique in which the results could indicate a significant influence on the relationship Hedonic Value of the behavioral intention with customer satisfaction as an intervening variable.